THE DEVELOPMENT OF ARABIC TRANSLATION PROFICIENCY THROUGH SKILL-BASED EXERCISES FOR STUDENTS IN THE ARABIC FOR HEALTH BUSINESS AND TOURISM PROGRAM AT YALA RAJABHAT UNIVERSITY - Saa , Masamdi (Journal of MCU Nakhondhat, 2025)
The research aims to 1) Develop and evaluate the effectiveness of Arabic translation skill exercises to meet the 75/75 standard criteria, 2) Compare the Arabic translation ability of students enrolled in the Arabic for Health Business and Tourism Program before and after using the researchers-developed Arabic translation exercises in the course “Development of Translation Skills” and 3) Examine students’ satisfaction with learning through the use of these exercises to enhance their Arabic translation skills. This study is experimental research and sample group consisted of 24 students enrolled in the second semester of the 2023 academic year, selected through purposive sampling. The research instruments included: 1) Eight sets of Arabic translation skill exercises, 2) an Arabic Translation proficiency test, and 3) A student satisfaction questionnaire using a five-point rating scale. Data analysis standard deviation, and t-test. The finding revealed that, 1) The effectiveness of the Arabic translation skill exercises was 77.24/78.33, meeting the established criteria, 2) Students’ Arabic translation ability after using the exercises was significance higher than before at the .05 level; and 3) Overall, students expressed a high of satisfaction with the exercises. The translation skill exercises developed from this research serve as a valuable tool for instructors in enhancing students' translation skills, which can be adapted for teaching and further improving students' academic translation proficiency.